What factors influence ambulance conveyance decisions when dealing with acutely unwell children? A systematic literature review - Simon Thomas Robinson; Will Broughton; Julia Williams (Emergency Medicine Journal, 2026)
Introduction Paramedics on an ambulance encounter acutely unwell children and are in a position to reduce demand on emergency departments through appropriate triage and non-conveyance decisions. How these decisions are made and what factors influence them are not completely understood. This review aimed to explore factors influencing decisions regarding child conveyance or non-conveyance. Methods A systematic review was conducted between November 2021 and October 2025 across five databases: PubMed, Medline, CINAHL (via EBSCOhost), Scopus and the Cochrane Registry of Controlled Trials. Studies published within the last decade were eligible for inclusion. Two authors independently screened titles and abstracts, and disagreements regarding article eligibility were arbitrated by the third author. Data were extracted using Covidence and quality appraised using Critical Appraisal Skills Programme checklists. Findings were synthesised using a narrative synthesis framework. Results Ten studies were included. Three overarching themes were identified: (1) the health system in which both ambulance service and families reside, including geographical location, resource availability, time of day and family preference as influencing factors; (2) child presentation, such that vital signs including respiratory distress, acuity and disease progression, as well as trauma, influenced decisions and (3) safety and risk, with factors affecting decisions including clinician education and experience, protocol adherence, access to shared support and clinical assessment and documentation. Conclusions Conveyance decisions are complex, shaped by child clinical presentation, perceived risk and paramedic judgement situated within the health system context (such as medical supervision). Current evidence neither justifies mandatory conveyance nor confirms that non-conveyance is clinically safe, despite both decisions occurring in practice. Future research should prioritise family perspectives, paramedic education and develop evidence-based non-conveyance protocols that support safe decision-making in the prehospital setting. PROSPERO registration number CRD420260310935.